(untitled) (Academic Journal of Internal Affairs, 2021)
The penal systems of the former socialist countries possess a certain similarity in their conceptions, the structure of their system of execution and their operation until the political change of regime, since all of them were based on Soviet patterns. Correctional efforts built on ideological education were lacking the capacity to answer questions related to the function of correctional institutions even before the change of regime. Taking into account the above, in this study I will endeavour to analyse the directions of corrections and correctional education before the change of regime and during the decade that followed it. Arrived: 15 May 2020 Accepted: 16 July 2020